Albergue educativo a través de la arquitectura adaptable para madres adolescentes en Kennedy, Ciudad Bolívar y Bosa, Bogotá. (2022)
An analysis of the social determinants with the greatest contribution to the occurrence of pregnancy in adolescence is carried out, as well as school dropout and lack of job opportunities as the greatest consequence of this problem. It is determined that the abandonment of the educational system due to adolescent motherhood is what favors the circles of poverty, given that unwanted early pregnancies in the absence of social support networks hinder opportunities for personal development and capacity building. , limit access to economic and social opportunities and have a negative impact on the formation of households between couples without sufficient autonomy and economic independence to assume the derived responsibility and individual and family strengthening. Knowing the actions that must be implemented to prevent pregnancy and paternity in adolescents, the next step should focus on designing and implementing academic spaces and accommodations that allow acting on the main needs of adolescents, particularly between 15 and 19 years of age. age. For this reason, through adaptable architecture, a preliminary project will be designed with spaces according to academic and housing needs to favor the development of adolescent mothers and their children.